Statistical analysis of discontinuities in solar wind ace data and comparison with intermittent mhd turbulence - Greco, A. (2009)
Fil:Dmitruk, P. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.